Faktor-faktor pergabungan bank dan implikasunya terhadap pengurusan sumber manusia - Dayangke Isneyah, Bte Awangku Serma (Universiti Malaysia Sarawak, (UNIMAS), 2002)
The objective ofthis study is to determine the factors that contribute to the merger ofbank in Malaysia and to determine its implications to human resource management. In this study, qUlllitative method in the form ofstructured interview were used to obtain feedbacks from ten respondents from the commercial bank's employees (Malayan Banking Berhad, Bank Bumiputra-Commerce, Hong Leong Bank and Bank Utama), representative from the Malaysian Industrial and Trade International (MIT/), representative from the Malaysian IndUStrial Development Fund (MIDF) and representative from the Sarawak Bank Employees Union (SBEU). Information was also obtained from books, journals, newspapers, articles from theinlernet, news bulletin and recordings ofinterview from the respondents. Data were analyzed according to the objectives and its implications to the human resource management. The findings showed that the factors that caused merger of banks were globalizatiOlI, liberalization, financial crisis, economy crisis and AFTA In conclusion, factors that contribute to the merger of banks also had impacts on human resource managemmt In the area of human resource pLanning, human resource development, compensation and benefits as well as industrial relation and labor.